The Continuity and the Culture Change of Pesantren in South Sumatra - Munir Munir (Ta'dib: Jurnal Pendidikan Islam, 2016)
This article entitled culture of pesantren (madrasah boarding schools) in South Sumatra. This article is the result of research in Pesantren Nurul Islam Ogan Ilir South Sumatra. It is based on the fact that many pesantren graduation create academicians from the Kiayi or Ulama. Therefore, this paper describe the characteristics of the culture of madrasah schools from anthropology-sociology aspects of education, with a phenomenological approach to research subjects are madrasah chairman, board of teachers, students and community supporters. The data collection techniques used documentation study, observation and in-depth interviews, and analysis of data using qualitative descriptive, with triangulation and contrasting techniques. Applying local knowledge systems in boarding school curriculum and integrated with Madrasah boarding school curriculum. Orientation discipline tends towards positive law than the laws of Personality Syara’. Clothing the students follow a uniform generally used in madrasah. For students wear clothes instead of the veil of windings. Artistic activities undertaken include: litany, muhad Barzanji, Tilawah al-Qur’an, calligraphy, and drum band. Artikel berjudul budaya pesantren (sekolah berasrama madrasah) di Sumatera Selatan. Artikel ini merupakan hasil penelitian di Pesantren Nurul Islam Ogan Ilir Sumatera Selatan. Hal ini didasarkan pada kenyataan bahwa banyak lulusan pesantren melahirkan akademisi dari kiayi atau Ulama. Oleh karena itu, makalah ini menggambarkan karakteristik budaya dari sekolah madrasah dari aspek antropologi-sosiologi pendidikan, dengan pendekatan fenomenologis dengan subyek penelitian kepala madrasah, dewan guru, siswa dan masyarakat sekitar. Teknik pengumpulan data yang digunakan studi dokumentasi, observasi dan wawancara mendalam, dan analisis data menggunakan deskriptif kualitatif, dengan triangulasi dan teknik kontras. Menerapkan sistem pengetahuan lokal dalam kurikulum pesantren dan terintegrasi dengan kurikulum sekolah berasrama Madrasah. Orientasi disiplin cenderung ke arah hukum positif dari hukum-hukum syara'. Pakaian para siswa mengikuti seragam pada umumnya yang digunakan di madrasah. Untuk siswa memakai pakaian bukan kain. Kegiatan seni yang dilakukan antara lain: litany, muhad Barzanji, Tilawah al-Qur'an, kaligrafi, dan drum band.